Формування і розвиток інноваційних методів профорієнтаційної роботи у вищому навчальному закладі - Бондар, Андрій Миколайович; Бондарь, Андрей Николаевич; Bondar, Andrii; Новик, Олексій Юлійович; Новик, Алексей Юльевич; Novik, Oleksii (My University, 2019)
UK: В статті розглянуто питання формування і розвитку інноваційних методів профорієнтаційної роботи у вищому навчальному закладі. EN: The article deals with the issues of formation and development of innovative methods of vocational guidance work at a higher educational institution.
Formation and development of innovational methods of professional work in the higher educational institution
Keywords: профорієнтаційна робота; самовизначення; ефективні методи; форми роботи; план заходів; популяризація інженерних професій; professional orientation work; self-determination; effective methods; forms of work; plan of activities; popularization of engineering professions